Best practices of promoting a positive school learning climate among headteachers of high performing primary schools and education blueprint 2013-2025 Malaysia - Salleh, Mohamad Johdi; Abu Bakar, Surayya (Open Access Publishing Group, 2018)
Abdullah, Y.A., (2001). The Holy Quran. United Kingdom: Wordworth Editions Ltd. Ahamad, Z., & Kasim, A. L. (2016). Organizational Climate as an editor of the relationship between Transformational Leadership and Innovative Behavior in school. International Journal of Scientific Research and Education,4(04). p5168-5176. Allen, N., Grigsby, B., & Peters, M. L. (2015). Does Leadership Matter? Examining the relationship among Transformational Leadership, School Climate, and Student achievement. International Journal of Educational Leadership Preparation, 10(2), 1-22. Bandyopadhyay, S., Cornell, D., & Konold, T. (2009). Validity of three school climate scales to assess bullying, aggressive attitudes, and help seeking. School Psychology Review, 38(3), 338-335. Bear, G. G., Gaskins, C., Blank, J., & Chen, F. F. (2011). Delaware school climate survey-Student: Its factor structure, concurrent validity, and reliability. Journal of School Psychology, 49, 157-174. Bear, G. G., Yang, C., & Pasipanodya, E. (2015). Assessing School Climate Validation of a Brief Measure of the Perceptions of Parents. Journal of psych educational assessment, 33(2), 115-129. Brand, S., Felner, R. D., Seitsinger, A., Burns, A., & Bolton, N. (2008). A large scale study of the assessment of the social environment of middle and secondary schools: The validity and utility of teachers’ ratings of school climate, cultural pluralism, and safety problems for understanding school effects and school improvement. Journal of School Psychology, 46, 507-535. Brand, S., Felner, R. D., Shim, M., Seitsinger, A., & Dumas, T. (2003). Middle school improvement and reform: Development and validation of a school-level assessment of climate, cultural pluralism, and school safety. Journal of Educational Psychology, 95, 570-588. Gottfredson, G. D., Gottfredson, D. C., Payne, A. A., & Gottfredson, N. C. (2005). School climate predictors of school disorder: Results from a national study of delinquency prevention in schools. Journal of Research in Crime & Delinquency, 42, 412-444. Hallinger, P., & Heck, R. (1996). Reassessing the principal’s role in school effectiveness: A review of empirical research, 1980–1995. Educational Administration Quarterly, 32(1), 5–44. Helen M. M. & Susan M. P. (2003). Principals’ leadership and schools’ performance: an integration of transformational and instructional leadership. Educational Administration Quarterly, 39, (3), 370-397. Houtte, M., V. (2005) Climate or culture? a plea for conceptual clarity in school effectiveness research. School Effectiveness and School Improvement, 16 (1), 71 – 89. Latif, Mohamad (2010) Principals Practice of Instructional Leadership at Secondary Schools Malaysia. PhD Thesis (Unpublished). Bangi: Universiti Kebangsaan Malaysa. Leithwood, k., Jantzi, D. and Steinbach, R. (1999) Changing Leadership for Changing Times, Buckingham: Open University Press. Loukas, A., Suzuki, R., & Horton, K. D. (2006). Examining school connectedness as a mediator of school climate effects. Journal of Research on Adolescence, 16, 491-501. Mc Carley, T. A., Peters, M. L., & Decman, J. M. (2016). Transformational leadership related to school climate a multi-level analysis. Educational Management Administration & Leadership, 44(2), 322-342. O’Malley, M., Voight, A., Renshaw, T. L., & Eklund, K. (2015). School climate, family structure, and academic achievement: A study of moderation effects. School Psychology Quarterly, 30(1), 142. Okorji, P. N., Igbokwe, I. C., & Ezeugbor, C. O. (2016). Relationship between school climate and principals' job performance in secondary schools. European Scientific Journal, 12(4). P55 Southworth, G. (2002). Instructional leadership in schools’ development: Reflections from research. School Organization, 12(2), 73–92. Surayya Abu Bakar. (2016). Practices of Positive School Learning Climate among Headteachers of High Performing Primary Schools in Malaysia. MEd Dissertation (Unpublished). Gombak: IIUM. Tajasom, A., Zainal, A., A. (2011) Principals' leadership style and school climate: teachers ' perspectives from principals’ leadership style and school climate: teachers’ perspectives from Malaysia. The International Journal of Leadership in Public Services. 7 (4), 314-333.